The importance of Dentistry in COVID-19 pandemic and the role of saliva as a diagnostic tool - MOURA,Nathalya Maria Vilela (2021)
ABSTRACT News of the symptoms caused by a coronavirus in humans began to be documented in December 2019, when several cases of pneumonia caused by the virus occurred in China. Studies are showing the increasing role of saliva and oral cavity in the transmission of the virus, because the receptors of epithelial cells in this region play a critical role by allowing the virus to enter those cells. The standard method to diagnose the coronavirus is based on the collection of samples in the nasopharynx and oropharynx to detect viral RNA. However, this method results in the interaction between health care professionals and patients, which increases risk of transmission; moreover, this collection can be painful for the patient and cause bleeding. As an alternative, diagnosis can be made using saliva, which only requires patients to deposit the saliva sample in a sterile container. Thus, the objective of this literature review is to present the main forms of contagion and to describe the diagnosis tools, emphasizing the risk that dental professionals are exposed to and, therefore, the growing need for better and faster diagnostic methods for coronavirus, especially using saliva. Medline, PubMed, SciELO, and Bireme databases were used for the literature search with the descriptors: Salivary diagnosis, COVID-19, and Contagion. The review explored the scientific race to develop more effective forms of diagnosis, including saliva tests, and prevention methods taking into account time, accessibility, and cost-benefit and, as a consequence, the role of dentistry has been continuously increasing.